DEVELOPMENT OF ASSESSMENT INSTRUMENT IN ACID-BASE PRACTICUM BASED ON CONTEXTUAL LEARNING - Thaufik A., Syarif Muhammad; ., Hairida; Lestari, Ira (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract: This experiment aims to produce assessment instrument in acid-base practicum in contextual learning on class XI. Form of research is Research and Development. The development model is procedural development. Data collected by using a feasibility questionnaire and teachersâ€™ product responses questionnaire. Results of feasibility analysis of questionnaire data obtained by the average percentage feasibility assessment instrument of 92.49% with criteria very high. Results of the data analysis of teachers' questionnaire responses obtained an average percentage of 91.25% teachers' response to the very high response criteria. Assessment instruments developed can be used as an assessment tool to assess the psychomotor and affective aspects with an average value of 96.35 and psychomotor aspects of the average value of the affective aspects of 95.83. Keywords: development, assessment instrument, contextual learning Abstrak: Penelitin ini bertujuan untuk menghasilkan instrumen penilaian dalam praktikum asam basa berbasis kontekstual di kelas XI yang layak digunakan. Bentuk penelitian yang digunakan adalahÂ penelitian pengembangan. Model pengembangan yang digunakan adalah model pengembangan prosedural. Pengumpulan data dilakukan dengan menggunakan angket kelayakan produk dan angket respon guru. Hasil analisis data angket kelayakan diperoleh persentase rata-rata kelayakan instrumen penilaian sebesar 92,49% dengan kriteria kelayakan sangat tinggi. Hasil analisis data angket respon guru diperoleh persentase rata-rata respon guru sebesar 91,25% dengan kriteria respon sangat tinggi. Instrumen penilaian yang dikembangkan dapat digunakan sebagai alat penilaian untuk menilai aspek psikomotor dan afektif dengan nilai rata-rata aspek psikomotor sebesar 96,35 dan nilai rata-rata aspek afektif sebesar 95,83. Kata kunci: pengembangan, instrumen penilaian, pembelajaran kontekstual.